2019
DOI: 10.1002/chem.201902419
|View full text |Cite
|
Sign up to set email alerts
|

Oxoborane Formation Turns on Formazanate‐Based Photoluminescence

Abstract: The synthesis of compounds containing multiple bonds to boron has challenged main-group chemists for decades. Despite significant progress, the possibility that the formation of such bonds can turn on photoluminescence hasr eceivedminimal attention. We report an oxoborane (B=O) complex that is electronicallys tabilized by af ormazanate ligand in the absence of significant steric bulk and, unlikethe common BX 2 (X = F, Cl) formazanate adducts,e xhibitsi ntense photoluminescence. The latter propertyw as rational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 85 publications
1
16
0
Order By: Relevance
“…We must therefore conclude that the t =0 μs excitation is to a different and higher‐energy state, however, it also does not have a clear 0–0 transition and additionally, each of the two states that we identify from the excitation spectra gives rise to the same emission spectrum (Figures B,D and A). Therefore, in Figure , we have shown the planar excited‐state relaxed geometry for S 1 * that has been previously reported as the emitting state . To assess the possible emission maximum from this relaxed state, we calculated the absorption spectrum from S 0 to S 1 * with a fixed planar geometry.…”
Section: Figurementioning
confidence: 97%
See 1 more Smart Citation
“…We must therefore conclude that the t =0 μs excitation is to a different and higher‐energy state, however, it also does not have a clear 0–0 transition and additionally, each of the two states that we identify from the excitation spectra gives rise to the same emission spectrum (Figures B,D and A). Therefore, in Figure , we have shown the planar excited‐state relaxed geometry for S 1 * that has been previously reported as the emitting state . To assess the possible emission maximum from this relaxed state, we calculated the absorption spectrum from S 0 to S 1 * with a fixed planar geometry.…”
Section: Figurementioning
confidence: 97%
“…A major proposed difference between the geometries of the electronic states of BODIPY dyes and BF 2 formazanate dyes is that the excited state geometry of the BF 2 formazanate dyes changes from the folded ground state to a planar, emissive excited state . In this paper, we examine the electronic origins of both the absorption and the emission spectral data for a prototypical BF 2 formazanate dye, 2 , which exhibits both a high molar absorptivity and emission quantum yield.…”
Section: Figurementioning
confidence: 99%
“…reported a formazanate‐based neutral boracarbonyl 6 stabilized by AlCl 3 (Scheme 3). [21f] Remarkably, examination of the photoluminescent properties revealed that 6 exhibits a small Stokes shift (50 nm) and has a photoluminescence intensity enhancement of more than 36‐fold ( Φ PL : 36 %), in comparison with P6 , which has large Stokes shift (174 nm) and was essentially found to be non‐emissive in solution ( Φ PL : <1 %). DFT analysis revealed that P6 is highly bent in the ground state and perfectly planar in the excited state, whereas the molecular geometry of photoexcited 6 undergoes little structural distortion and resembles its ground state.…”
Section: Group 13 Carbonyl Analoguesmentioning
confidence: 99%
“…A second non-radiative decay pathway was uncovered when the Lewis-acid-supported oxoborane (BQO) complex 64 was isolated (Scheme 26). 77 Access to this species required a halide exchange reaction between BF 2 triarylformazanate 59b (Ar 1 /Ar 5 = p-tolyl; R 3 = Ph) and BCl 3 to generate BCl 2 complex 63. The BCl 2 unit in compound 63 was subsequently converted to the oxoborane by treatment with one equivalent of AlCl 3 and H 2 O.…”
Section: Group 12 (Zn)mentioning
confidence: 99%
“…The photoluminescence characteristics of oxoborane 64 support this hypothesis, as the formation of the BQO unit turns on photoluminescence (l PL = 636 nm, F PL = 36%). 77 The origin of this behavior lies in the fact that both the ground and excited states of compound 64 adopt a planar structure as the result of sp 2 hybridization at boron, thus limiting structural reorganization upon photoexcitation and attenuating non-radiative decay. Based on these studies, it is reasonable to assume that 62,64,65,70,73 Compound 78 it may not be surprising that BF 2 formazanates have been shown to be biocompatible during their use as cell-imaging agents (Fig.…”
Section: Group 12 (Zn)mentioning
confidence: 99%